2018
DOI: 10.1016/j.nicl.2018.09.030
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of different three-dimensional subcortical human brain atlases for DBS –lead localisation

Abstract: BackgroundAccurate interindividual comparability of deep brain stimulation (DBS) lead locations in relation to the surrounding anatomical structures is of eminent importance to define and understand effective stimulation areas. The objective of the current work is to compare the accuracy of the DBS lead localisation relative to the STN in native space with four recently developed three-dimensional subcortical brain atlases in the MNI template space. Accuracy is reviewed by anatomical and volumetric analysis as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 35 publications
0
35
0
Order By: Relevance
“…Therefore, inferior congruence of the manual MRI based atlases with the manual segmentation compared to the MRI-based DA might be caused by the different origins of the atlases. Furthermore, it has recently been shown that DA shows significant discrepancies compared to electrophysiologically defined STN [18]. Therefore, it is questionable whether this atlas should be used as reference.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Therefore, inferior congruence of the manual MRI based atlases with the manual segmentation compared to the MRI-based DA might be caused by the different origins of the atlases. Furthermore, it has recently been shown that DA shows significant discrepancies compared to electrophysiologically defined STN [18]. Therefore, it is questionable whether this atlas should be used as reference.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Recently, others confirmed accuracy of the atlas based on intraoperative microelectrode recordings and showed that it matched electrophysiological data better than three other atlases of the STN (Nowacki et al, 2018). Finally, the motor functional zone of the atlas was defined using diffusion weighted imaging data acquired on specialized MR hardware (Setsompop et al, 2013) and cross-validated using both healthy controls and PD data (Ewert, Plettig, et al, 2018).…”
Section: Limitationsmentioning
confidence: 89%
“…Still, the amount of error introduced by nonlinear registrations remains unclear. Some validation of electrode localizations in standard space were made using electrophysiology by various groups (Horn et al, 2017b;Neumann et al, 2017;Nowacki et al, 2018;Tinkhauser et al, 2019;van Wijk et al, 2017). For instance, agreement between electrophysiology-defined and atlas-defined boundaries in standard space showed high agreement across 303 microelectrode recording sites when localizing recording-sites using Lead-DBS (Rappel et al, 2019).…”
Section: Limitationsmentioning
confidence: 99%